NEET in Germany: Labour Market Entry Patterns and Gender Differences - Christian Brzinsky-Fay (The Dynamics of Marginalized Youth, 2022)
This chapter aims at assessing the Not in Employment, Education or Training (NEET) youth in Germany, where one finds a strong institutionalized apprenticeship system, a relatively high stratification of the educational system and a gendered vocational education and training system. The dependent variable is the occupational status at the age of 30 measured by the International Socio-Economic Index of Occupational Status. The independent variables are the socio-economic background information and the NEET patterns or respectively the cumulative NEET length. Germany constitutes an interesting case when looking at the longitudinal patterns of youths who experience NEET periods, for several reasons. In international comparison, the connection between education system and the labour market in Germany is quite structured.
Keywords: 300